Investigating International, Source and Target Cultures in the University English Textbook’’ Headway Plus Series’’ - Hasan, Hanan Abdallah; Muhammed, Ibtisam Jasim (Journal of Tikrit University for Humanities, 2025)
Language and culture are inseparably linked and bonded together. Cultural content analysis is typically included in language acquisition textbooks. This study is a content analysis of cultural content of the university English textbook ’’Headway Plus series’’ (intermediate) students’ book. This study aims to recognize the extent of the representation of the three cultures: international, source and target culture in the textbooks. This study uses descriptive qualitative method especially content analysis to analyze the textbook. This study adopts the model from Cortazzi and Jin to reveal about the representation of the three types of cultures: International, Source and Target culture. The analysis of textbook has revealed some major findings. Firstly, the cultures are mostly represented by names of people, countries, texts, visuals and activities. Secondly, Headway plus for Intermediate dominantly presents through Target culture compared to International and Source culture. In addition, this study also finds out that there is an unbalanced quantity among presented types of cultures as the Source culture is almost neglected in the textbook. Consequently, this study suggests for supplementing the course with teacher prepared materials corresponding to different cultures to reach the balance presentation among Source, Target and International culture. Finally, the study ends up with some conclusions, recommendations, and suggestions for further researches.